Neurocognitive effects in welders exposed to aluminium. (May 2014) - Giorgianni, Concetto Mario; D'Arrigo, Graziella; Brecciaroli, Renato; Abbate, Adriana; Spatari, Giovanna; Tringali, Maria Antonietta; Gangemi, Silvia; Luca, Annamaria De
Objectives: Various authors who studied the effects of aluminium (Al) exposure on the neurocognitive system in the last 30 years have reached different and often contradictory conclusions. The aim of this study is to help clarify the effects that the metal causes on cognitive ability in a group of naval welders exposed to Al. Methods: The study was performed on a sample of 86 male Al welders in a shipyard in Messina. The average value of environmental Al, recorded in the workplace, was 19.5 mg/m 3 . The blood levels of Al, zinc, manganese, lead and chromium were monitored in all the subjects. The reagents used for the neuropsychic study were the Wechsler Memory Scale (WMS), the Colour Word Test or Stroop Test and the Test of Attention Matrixes. The results were compared with those obtained in a similar control group not exposed to Al and with an Al-b value of 6.93 g/l. Results: For all the mental reagents used, the reply is obtained in the sample of exposed subjects showed decreased cognitive response with regard to attention and memory performance. The comparison between the individual tests showed greater sensitivity of performance studied using the WMS and the Stroop Test compared with the Test of Attention Matrixes. The alterations encountered in the cognitive functions studied increased proportionally to time of exposure and quantity of metal absorbed. Conclusion: The study confirmed that occupational exposure to Al causes alteration in cognitive responses that are more evident in complex functions.